'Durate variant with clinical signs' has alpha1 -antitrypsin genotype ZZ. Issue 1 (February 1976) - Weitkamp, L R; Sayre, J W; Schwartz, R H; Doherty, R; Khera, S A
Abstract : A patient with neonatal jaundice and cirrhosis who was previously reported homozygous for the Durate variant of galactose-1-phosphate uridyl transferase has the ZZ genotype for alpha1-antitrypsin. A sister of the patient, also with ZZ genotype, is less severly affected with liver disease and is a heterozygote for the Durate variant. Since a number of patients with ZZ genotype of alpha1-antitrypsin have been previously reported to have liver disease, the latter genotype is the more probable explanation for the patients' clinical state. A question is raised, however, whether the Duarte variant may be specifically associated with the development of liver disease in ZZ individuals.